2019
DOI: 10.1111/ans.15427
|View full text |Cite
|
Sign up to set email alerts
|

Study of changes of obesity‐related inflammatory cytokines after laparoscopic sleeve gastrectomy

Abstract: Background: Chronic inflammation in adipose tissue may play a substantial role in the pathogenesis of obesity-related metabolic disorders. The present study aims to evaluate the changes in adipocytokines, bile acids, fibroblast growth factor 19 (FGF-19) and proinflammatory cytokines 6 months after laparoscopic sleeve gastrectomy (LSG). Methods: This prospective study included 75 obese patients with body mass index >35 kg/m 2 who underwent LSG. All patients were recruited preoperatively and followed up post-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…Similarly, Salman et al demonstrated that the levels of serum adiponectin significantly increased, while the levels of serum leptin, resistin, CRP, plasminogen activator inhibitor-1 and serum amyloid-A significantly decreased at 6 months after SG [34]. In contrast to previous studies [18,19,34], we observed no statistically significant change in serum adiponectin levels. This might be explained by a small sample size.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Similarly, Salman et al demonstrated that the levels of serum adiponectin significantly increased, while the levels of serum leptin, resistin, CRP, plasminogen activator inhibitor-1 and serum amyloid-A significantly decreased at 6 months after SG [34]. In contrast to previous studies [18,19,34], we observed no statistically significant change in serum adiponectin levels. This might be explained by a small sample size.…”
Section: Discussioncontrasting
confidence: 72%
“…Zhu et al demonstrated a reduction in leptin, CRP and IL-6 in patients with morbid obesity and subclinical hypothyroidism 12 months following SG [33]. Similarly, Salman et al demonstrated that the levels of serum adiponectin significantly increased, while the levels of serum leptin, resistin, CRP, plasminogen activator inhibitor-1 and serum amyloid-A significantly decreased at 6 months after SG [34]. In contrast to previous studies [18,19,34], we observed no statistically significant change in serum adiponectin levels.…”
Section: Discussionmentioning
confidence: 96%
“…However, levels of IL‐6 at the systemic level increased 3 months after VSG‐induced weight loss, showing that there is a distinct mechanism of IL‐6 regulation occurring at the local compared with systemic level, likely involving other tissues. While studies have shown a reduction in pro‐inflammatory cytokines including IL‐6 one year after sleeve gastrectomy or no change in IL‐6 serum levels 6 months after VSG or Roux‐en‐Y gastric bypass (RYGB), to our knowledge, levels of systemic IL‐6 have not been shown to increase after VSG‐induced weight loss.…”
Section: Discussionmentioning
confidence: 75%
“…104 Many clinical studies have also shown that inflammatory factors and TLR receptors are significantly reduced after surgery, but adipokines like leptin and adiponectin have not shown consistent results. [105][106][107] Some bariatric surgery patients regained weight after weight loss, but the inflammatory factors continued to decrease, indicating that bariatric surgery may have a long-term effect on inflammation control. 108…”
Section: Anti-inflammatory Therapeutic Effect Of Bariatric Surgerymentioning
confidence: 99%